`h(s) = (s^3 - 2)^2` Find the derivative of the algebraic function.

Textbook Question

Chapter 2, 2.3 - Problem 31 - Calculus of a Single Variable (10th Edition, Ron Larson).
See all solutions for this textbook.

1 Answer | Add Yours

hkj1385's profile pic

hkj1385 | (Level 1) Assistant Educator

Posted on

Note:- If y = x^n ; where n = constant ; then dy/dx = n*x^(n-1)

Now,

`h(s) = (s^3 - 2)^2`

`h'(s) = (2)(3s^2)*(s^3-2)^1`

`or, h'(s) = (6s^2)*(s^3 - 2)`

`or, h'(s) = 6s^5 - 12s^2`

``

` `

We’ve answered 318,976 questions. We can answer yours, too.

Ask a question